Analysis of Attack Techniques for Competing Category Athletes in the 2024 Kediri District Branch Women's Krida PSHT Final Match - Amanda Sheila Shafira; Moh. Nurkholis; Rizki Burstiando (NUSANTARA SPORTA: Jurnal Pendidikan dan Ilmu Keolahragaan, 2024)
This research examines the most effective attack techniques for scoring points in the women's final match of the Krida PSHT Kediri district branch in 2024. The study uses a quantitative descriptive approach with a survey method. The instrument employed was a questionnaire. The population consisted of eight female athletes from the youth class finalists in the competition's A, B, C, and D categories. A total sampling technique was applied, involving all eight athletes as respondents.The results revealed a total of 174 attacks during the final matches. Among these, punches were the most common attack, occurring 47 times (27%), followed by crescent kicks with 45 occurrences (25.9%), front kicks 34 times (19.5%), and falls 25 times (14.4%). Back kicks (T) were executed 18 times (10.3%), while cuts were used minimally, with two occurrences (1.2%) and three occurrences (1.7%), respectively. The findings highlight the dominance of punches and crescent kicks as the most frequently used and potentially effective techniques in women's Krida PSHT competitions. This information provides valuable insights for athletes and coaches to strategize and improve performance in future matches